Exploring the Economic Hypothetical for Downhill Belt Conveyors Equipped with Three-Phase Active Front-End Load Converters - Daniel Chelopo; Kapil Gupta (Technologies)
This paper integrates empirical assessments of energy recovery in downhill belt conveyor systems with rigorous theoretical modeling and economic analysis. An alternative approach for capturing and transforming the potential energy of a descending conveyor into electrical energy is proposed using an active front-end (AFE) load energy recovery system. Adjusting the drive configuration from a standard direct-on-line (DOL) system to a regenerative AFE converter, the conveyor’s excess kinetic energy can be fed back into the grid. The investigation shows that operating a 300 kW downhill conveyor at full capacity would consume about 142,800 kWh per month in a conventional setup. However, at 90% of the maximum capacity over 17 h per day (~476 h per month), the conveyor with an AFE system produces a regenerative power of 188 kW (negative demand), yielding a net generation of 89,488 kWh per month. The results indicate that integrating a regenerative AFE control system can achieve energy savings of approximately 37% compared to a non-regenerative system. The key economic indicators, including lifecycle cost, payback period, and net present value, confirm the financial viability of the proposed system over a 20-year span.